The Strange Career of J. Frank Norris: Or, Can a Baptist Democrat Be a Fundamentalist Republican? - Hankins, Barry (Church history, 1992)
From the 1920s onward, many individuals and denominations have referred to themselves as Baptist-fundamentalists or fundamentalist-Baptists. Increasingly, however, scholars are emphasizing the stark contrast between fundamentalism and Baptist life.1 More than any other, the life of J. Frank Norris stands as an example of the tension, if not irreconcilability, between the two camps. The enigmatic, or perhaps oxymoronic, nature of Norris's theological life was paralleled by his political endeavors in which he claimed to be a Democrat, but almost always supported Republican candidates. Being from Texas, it was natural that Norris would begin his career as a Baptist Democrat. In time, however, he evolved into a fundamentalist Republican. He actually attempted to be a fundamentalist-Baptist religiously and a Republican-Democrat politically. The fusion of these two religious traditions was no less problematic than fusion of the political parties.